Empirical analysis of the relationship between purchasing managers index and bist industrial index under structural breaks - Emrah Şahin; Selim Güngör; Süleyman Serdar Karaca (Financial Studies, 2020)
The purpose of the study is to put forward the long-term and causality relationship between the BIST Industrial Index and the Purchasing Managers Index (PMI) for the period January 2008-December 2018 in Turkey. First of all,the existence of a long-run relationship between variables has been investigated with cointegration test. It has been determined that there is a long-run relationship between series. For this reason, the coefficient estimation for the long-run relationship between the series has been made a prediction with the Fully Modified Ordinary Least Squares cointegration coefficient estimator. Finally, the existence of causality relationship between the series has been investigated with theasymmetric causality test in the study and it has been determined that there is a unidirectional causality relationship from PMI to BIST Sinai index in terms of positive and negative shocks. Therefore,with this study it can be said that the PMI is a predictor of stock prices.
Keywords: C22; C53; D53; 330; BIST Industrial Index; PMI; Cointegration Test with Multiple Structural Breaks; Asymmetric Causality Test